SURGICAL TREATMENT OF CHRONIC ELBOW JOINT INJURIES WITH THE VOLKOV-OGANESIAN APPARATUS - Tilyakov A.B. (Scholar Express Journals, 2023)
Patients who have undergone severe elbow joint trauma often develop various complications. Heterotopic ossification is considered to be the most severe complication; it leads to severe impairment of the upper extremity function due to the formation of severe contractures and ankylosis in the elbow joint. The paper presents the results of surgical treatment of the elbow joint in a patient with "immature" ossification against the background of aged dislocation of the forearm bones, non-unionized fracture of the radial head, and stage II osteoarthritis. Analysis of the outpatient follow-up of the patient after injury revealed gross diagnostic and treatment errors. As a result of medical errors, inadequate treatment of injuries in the early stages after injury was prescribed, which contributed to the formation of heterotopic ossification and resulted in functional failure of the joint. During surgery, the ossification located in the ulnar fossa was removed via a small posterior access to the elbow joint, the remaining tissues of the joint were not affected, thorough hemostasis was performed, and a Volkov-Oganesian articulation-distraction device was applied to provide physiological range of motion in the elbow joint. Postoperative longterm rehabilitation ensured restoration of the elbow joint function with the patient's return to professional activities.
Keywords: elbow joint; arthroplasty; contracture; ankylosis